Evaluation of Dairy Cow Milk Production Based on Temperature Humidity Index (THI) - Adhyatma, Muhammad; Ahmad, Yanuar; Kusuma, Satria Budi; Permadi, Herlina Irawati; Fajrin, Eistifani (Jurnal Sains dan Teknologi Industri Peternakan, 2024)
This study aims to assess the impact of environmental temperature on the milk production of PFH dairy cows. The research site is located at an altitude of 187 meters above sea level, indicating relatively high levels of temperature and humidity. The average temperatures range between 23-30°C and the humidity levels range between 63-86%. Both elevated temperature and humidity can have an influence on milk production. The findings of this study indicate that the barn's Temperature-Humidity Index (THI) falls within the mild stress category. The milk production results for PFH dairy cows ranged from 3-6 liters per head per day in the morning, and 1.5-3 liters per head per day in the afternoon. However, it should be noted that this production level is still below the genetic standards. Other factors such as feed, management practices, and animal health also play a role in milk production. Regression analysis suggests a correlation between environmental temperature (THI) and milk production, although this correlation is not statistically significant. This lack of statistical significance may be attributed to the influence of various other factors on milk production, such as feed type and management practices. Therefore, in order to enhance the milk production of PFH dairy cows, it is necessary to develop a more comprehensive understanding of these contributing factors.